Late grafted kidney dysfunction: morphological structure, criteria for diagnosis - E. S. Stolyarevich; N. A. Tomilina (Трансплантология (Москва), 2018)
Grafted kidney abnormalities include a wide spectrum of diseases that differ in their nature, mechanisms of development, and rates of progression. In the early period after renal transplantation, the most important cause of graft dysfunction remains to be acute rejection that results from a recipient's immunological response to a donor's transplantation antigens and develops with the activation of both cellular and humural immune responses. In the late periods, one of the main causes of late graft losses is chronic graft dysfunction, the morphological substrate of which is progressive nephrosclerosis. The development of graft nephrosclerosis is generally associated with the combined effects of a large variety of both immune and nonspecific factors; however, the morphological features make it possible to identify the preponderance of this or that mechanism in its origin and, in this connection, individual nosological entities. The latter include chronic rejection, calcineurin inhibitorinduced nephrotoxicity, and nephrosclerosis caused by rejection-unassociated conditions, such as ischemic-reperfusion lesion, obstructive nephropathy, viral graft damage, etc. Moreover, as more time elapses after renal allotransplantation (RAT), there is a higher incidence of recurrent and de novo diseases, the most common types of which are IgA-nephropathy, focal segmental glomerulosclerosis, membranous nephropathy, diabetic nephropathy, etc. Puncture biopsy using immunofluorescence and electron microscopy is the gold standard of the diagnosis of graft kidney abnormalities since only the morphological verification of the diagnosis permits adequate immunosuppressive therapy, by improving the long-term results of RAT. The paper presents diagnostic criteria and morphological features of different types of renal graft diseases.